A small protein encoded by a putative lncRNA regulates apoptosis and tumorigenicity in human colorectal cancer cells - Xiao Ling Li; Lőrinc Pongor; Wei Tang; Sudipto Das; Bruna R Muys; Matthew F Jones; Sarah B Lazar; Emily A Dangelmaier; Corrine CR Hartford; Ioannis Grammatikakis; Qinyu Hao; Qinyu Sun; et al. (eLife, 2020)
Long noncoding RNAs (lncRNAs) are often associated with polysomes, indicating coding potential. However, only a handful of endogenous proteins encoded by putative lncRNAs have been identified and assigned a function. Here, we report the discovery of a putative gastrointestinal-tract-specific lncRNA (LINC00675) that is regulated by the pioneer transcription factor FOXA1 and encodes a conserved small protein of 79 amino acids which we termed FORCP (FOXA1-Regulated Conserved Small Protein). FORCP transcript is undetectable in most cell types but is abundant in well-differentiated colorectal cancer (CRC) cells where it functions to inhibit proliferation, clonogenicity, and tumorigenesis. The epitope-tagged and endogenous FORCP protein predominantly localizes to the endoplasmic reticulum (ER). In response to ER stress, FORCP depletion results in decreased apoptosis. Our findings on the initial characterization of FORCP demonstrate that FORCP is a novel, conserved small protein encoded by a mis-annotated lncRNA that regulates apoptosis and tumorigenicity in well-differentiated CRC cells.